2018
DOI: 10.1002/smtd.201800183
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Critical Role of Titanium in Layered Manganese‐Based Oxides toward Advanced Sodium‐Ion Batteries via a Combined Experimental and Theoretical Study

Abstract: interest on accounts of its low cost and abundance of sodium resource. [3][4][5] Additionally, the replacement of Cu with Al as the anode current collector can further reduce the cost and simplify the manufacturing process. [6] The high-performance cathode materials of sodium-ion batteries have been widely studied, [7] including layered oxides, [8,9] Prussian blue analogues [10,11] and polyanion materials. [12,13] Owing to simple manufacturing methods and reversible insertion/extraction, layered oxide Na x MeO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Meanwhile, sodium ions can be divided into Na e and Na f due to their located positions, which share the edges and faces with the transition metal octahedral, respectively. 29,39 For s-NaLiMMCO, transition metals locate in oxygen layers while Li occupies part of the sodium position. 38 The valence states of the transition metals in s-NaLiMMCO obtained by XPS measurement are depicted in Figure 2b–d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, sodium ions can be divided into Na e and Na f due to their located positions, which share the edges and faces with the transition metal octahedral, respectively. 29,39 For s-NaLiMMCO, transition metals locate in oxygen layers while Li occupies part of the sodium position. 38 The valence states of the transition metals in s-NaLiMMCO obtained by XPS measurement are depicted in Figure 2b–d.…”
Section: Resultsmentioning
confidence: 99%
“…This material only shows very low capacity decay after long cycling. 29 Li et al reported a P2-Na 0.67 Mn 0.65 Ni 0.2 Co 0.15 O 2 material, which exhibited a superior capacity of 155 mA h g –1 when cycled at 12 mA g –1 and an excellent rate performance even when cycled at high rate density. 30 Many previous research results indicate that doping with Li, Zn, Mg, Al, and so on can greatly ameliorate the electrochemical properties of the original cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ti-doping can restrain the shrinkage or elongation of the MnO octahedral structure, thus minimize the Jahn-Teller distortion for Mn atoms surrounded by titanium. [244] The low valent Mg 2+ doping can also suppress structural distortion by increasing the average charge state of Mn-ion to close to 4+, [245] and the Mn 4+ is Jahn-Teller inactive. However, recent studies show that the impact of Jahn-Teller distortion on Mn-based materials is not all negative.…”
Section: Jahn-teller Distortionmentioning
confidence: 99%
“…[248] Recent studies further show that vacancy defects in graphene coating layer can bond with Mn-ions to prevent them dissolve into electrolyte. [222,249] Elemental doping was reported to be able to suppress Mn-dissolution in oxide materials for SIBs [244] and ZIBs. [250] Some studies ascribed it to the changed local atomic environment that derived from doping mitigates Jahn-Teller distortion, and thus suppress Mn-dissolution.…”
Section: Mn Dissolutionmentioning
confidence: 99%
“…[17][18][19] Ti doping can suppress Jahn-Teller distortion through reducing the bond length variation along the axial and equatorial directions. 15,20 Ti dopant is also known to enhance oxygen retention in layered oxides due to its strong chemical bonding with oxygen. 21,22 Such structural stabilization through doping chemistry may also be beneficial towards the reversibility of the oxygen redox process.…”
mentioning
confidence: 99%